An efficient tool for solving two‐dimensional fuzzy fractional‐ordered heat equation. Issue 2 (29th October 2020) - Arfan, Muhammad; Shah, Kamal; Abdeljawad, Thabet; Hammouch, Zakia
Abstract: In this work we develop an algorithm to compute analytical solution for a two‐dimensional fuzzy heat equation involving external source term with fractional order. The algorithm is based on the Homotopy perturbation method: The required result is computed in series form which is rapidly convergent to the exact solution. Examples are given to verify the result, which are compared with the exact solution to illustrate the efficiency and the capability of the proposed method.